INTEGRAL EQUATION METHOD FOR 3D MODELING OF ELECTROMAGNETIC FIELDS IN COMPLEX STRUCTURES WITH INHOMOGENEOUS BACKGROUND CONDUCTIVITY - Zhdanov M.S.; Yoshioka K.; Lee S.K. (My University, 2006)
We present a new formulation of the integral equation (IE) method for three-dimensional (3D) electromagnetic (EM) modeling in complex structures with inhomogeneous background conductivity (IBC). This method overcomes the standard limitation of the conventional IE method related to the use of a horizontally layered background only. The new 3D IE EM modeling method still employs the Green's functions for a horizontally layered 1D model. However, the new method allows us to use an inhomogeneous background with the IE method. We also introduce an approach for accuracy control of the IBC IE method. This new approach provides us with the ability to improve the accuracy of computations by applying the IBC technique iteratively. This approach seems to be extremely useful in computing EM data for multiple geologic models with some common geoelectrical features, like terrain, bathymetry, or other known structures. It may find wide application in an inverse problem solution, where we have to keep some known geologic structures unchanged during the iterative inversion. The method was carefully tested for modeling the EM field for complex structures with a known variable background conductivity. The effectiveness of this approach is illustrated by modeling marine controlled-source electromagnetic (MCSEM) data in the area of Gemini Prospect, Gulf of Mexico. © 2006 Society of Exploration Geophysicists.
Keywords: GEOMAGNETISM; GEOPHYSICAL TECHNIQUES; INTEGRAL EQUATIONS; INVERSE PROBLEMS; TERRESTRIAL ELECTRICITY